Efforts to Prevent Risk Factors for Stunting in Toddlers Through Socialization of Fish-Based Food Processing in Bangko Village - Ibrahim, Abu Rahmat; Hasbullah , Hasbullah; Rasulu , Hamidin; Albaar , Nurjanna; Abdullah , Hayun; Husen, Janiah (Agrikan Jurnal Agribisnis Perikanan, 2025)
Stunting is one of the global nutritional problems in children, where around 161 million toddlers in the world experience stunting. Education and family understanding of nutrition have an impact on stunting. West Halmahera Regency ranks first in the number of stunted toddlers compared to other districts/cities in North Maluku. The prevalence of children under five (toddlers) who have short and very short nutritional status in 2018 was 35.26%. When viewed from the consumption patterns of toddlers in Bangko Hamlet, they generally consume more than one type of carbohydrate, including rice, cassava, and sago. Most of them only consume vegetable side dishes such as tempeh and tofu 2-6 times per week. As for animal-based dishes, more than 90% of them consume these every day and at least once a day. The general objective of this PKM is to improve the knowledge and skills of mothers of toddlers in compiling menus and processing local fish-based food ingredients as an effort to prevent stunting in toddlers. The method used in this study was to socialize and demonstrate fish-based menus in an effort to reduce stunting rates as a form of prevention. The results of community service can be seen from the increase in community knowledge in three aspects: knowledge of efforts to prevent stunting (89.1%), knowledge of making banana fish porridge (73%), and knowledge of fish roulade with the addition of carrots (67.6%).